PENGGUNAAN ALAT-ALAT LABORATORIUM UNTUK MENINGKATKAN PEMAHAMAN KONSEP DALAM PEMBELAJARAN IPA DI SMP NEGERI 14 KOYA KOSO JAYAPURA - Tatang Sutarman; Maklon Warpur (JURNAL PENGABDIAN PAPUA, 2019)
The aims of this service were: (1) To improve the understanding of science’s concept for teachers and pupil; (2)  To improve the awereness and interest of students to study science; (3) To improve the soft skill of science teacher to create the simple and interesting learning program. The methods used this time was using a tools gathered around the school. Some equipments from laboratory were also used to support the activity. We can conclude that our activity were success in pulling out the awareness of students to learn sciences. We can measures it from their enthusiasm of the pupils when doing the exercise using gathered tolls and laboratory equipment. Keywords: science, study, equipments, laboratory, Jayapura